Methicillin-Resistant Staphylococcus aureus Infections in Human Immunodeficiency Virus-Infected Children and Adolescents - George K. Siberry; Toni Frederick; Patricia Emmanuel; Mary E. Paul; Beverly Bohannon; Travis Wheeling; Theresa Barton; Mobeen H. Rathore; Kenneth L. Dominguez (AIDS Research and Treatment)
Background. Methicillin-resistant Staphylococcus aureus (MRSA) infection incidence has increased in healthy US children. Our objective was to evaluate MRSA incidence and correlates in HIV-infected youth. Methods. The CDC-sponsored LEGACY study is a US multicenter chart abstraction study of HIV-infected youth. We identified MRSA infections among participants with ≥1 visit during 2006. We used bivariate and multivariable analyses to compare sociodemographic and HIV clinical factors between MRSA cases and noncases. Results. Fourteen MRSA infections (1 invasive, 12 soft tissue, 1 indeterminate) occurred among 1,813 subjects (11.1 infections/1,000 patient-years (PY), 95% CI: 11.06–11.14). Most (86%) isolates were clindamycin susceptible. Compared with noncases, MRSA cases were more likely older (17 versus 14 years), black (100% versus 69%), behaviorally HIV infected (43% versus 17%), and in Maryland (43% versus 7%) and had viral loads (VL) >1000 copies/mL (86% versus 51%) and lower mean CD4% (18% versus 27%) (all P<0.05). In multivariate analysis, independent risk factors were Maryland care site (adjusted odds ratio (aOR) = 9.0), VL >1000 copies/mL (aOR = 5.9), and black race (aOR undefined). Conclusions. MRSA occurred at a rate of 11.1 infections/1,000 PY in HIV-infected youth but invasive disease was uncommon. Geographic location, black race, and increased VL, but not immunosuppression, were independently associated with MRSA risk.